Sulfasalazine-Loaded Copper-Tannic Acid Coordination Nanozyme Enables ROS Scavenging and Immunomodulation for Inflammatory Bowel Disease Therapy - Yan, Jian-Hua; Liang, Chun-Xiao; Ma, Ran-Ran; Li, Bo-Jia; Chen, Qi-Wen; Li, Wen; Zeng, Xuan; Zhang, Xian-Zheng (Advanced healthcare materials, 2024)
Inflammatory bowel disease (IBD) is associated with elevated levels of reactive oxygen species (ROS) and an increased expression of proinflammatory cytokines. Anti-inflammatory drugs, monoclonal antibodies, and immunomodulators are commonly employed to control the inflammatory response in the management of IBD. Here, a copper and tannic acid (TA) coordination nanozyme (CuTA) loaded with sulfasalazine (SSZ-CuTA) is synthesized for the treatment of IBD by simultaneous scavenging ROS and immunosuppression. The CuTA exhibits both dismutase-like activity and catalase-like activity, making it efficient at scavenging ROS. These nanozymes can efficiently traverse gastric acid and subsequently exert their effects within the intestinal tract. It is verified that SSZ-CuTA can restore intestinal mucosal and goblet cells to a healthy state by effectively eliminating ROS and reducing the pro-inflammatory factors in a mouse IBD model. Overall, the SSZ-CuTA will offer a promising alternative treatment for patients suffering from IBD where excessive ROS and high inflammation coexist.